Menjaga Tradisi: Tingginya Animo Suku Banjar Bersalin kepada Bidan Kampung - . Serilaila; Atik Triratnawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This article is an attempt to explain why the bidan kampung exists among the Banjarese, despite the existence of midwives. The data for the research were obtained from interviews with selected mothers, bidan kampung, midwives and religious leaders from the Binuang district, South Kalimantan. The results indicate that nominal or symbolic economic factors for their services and such psychological aspects as patience and peacefulness were determinant in the choice of bidan kampung. Social relationship among bidan kampung and the clients in rural society contribute to their existence.